Mapping the Landscape of Hospitality and Tourism: A Bibliometric Study (2000–2025) - Prashotam; Singh, Karnail; Jeet, Vikram; Shiv Raj (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In the Last two decades, the hospitality and tourism sector has undergone considerable advancements in both academic and professional realms, thereby necessitating a systematic analysis of its research landscape. This bibliometric study employs data sourced from the Scopus database and utilizes sophisticated bibliometric tools, including the Bibliometrix R package and VOSviewer, to assess global scholarly output. The investigation examines research trends, prolific authors, influential journals, leading institutions, and international collaboration networks. The results indicate that the United States and China are the foremost contributors, with the U.S. generating the highest volume of publications and China exhibiting a superior average citation impact. Thematic mapping reveals a sustained interest in critical topics such as "Tourism," "Hospitality Industry," "Covid-19," and "Sustainability." Furthermore, keyword analysis suggests an increasing focus on strategic management, digital transformation, and resilience. Key journals, including the International Journal of Contemporary Hospitality Management and Tourism Management, are identified as pivotal in the dissemination of knowledge. Prominent academics are recognized for their significant advance in discipline including Law Rob and koseoglu Mehmet Ali. The research also projects a forecast for a two-decade publication projecting continuous growth in the discipline until 2045. This extensive investigation enhances the understanding of the intellectual framework, thematic evolution, and global dissemination of research in the fields of hospitality and tourism, thereby providing valuable insights for future research endeavours and strategic planning.